2015
DOI: 10.2105/ajph.2015.302884
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries: Racial and Ethnic Disparities Among North Carolina Kindergarten Students

Abstract: Racial/ethnic oral health disparities exist among kindergarten students in North Carolina as a whole and regardless of school's poverty status. Furthermore, disparities between White and Black students are larger in nonpoor schools than in poor schools. Further studies are needed to explore causal pathways that might lead to these disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…This phenomenon has been described as double disadvantage in the scientific literature. Double disadvantage has also been reported in previous studies on oral epidemiology [21,22]. Oral health disparities related to racial/ethnic background among children were greater in wealthy schools than in deprived schools [21].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This phenomenon has been described as double disadvantage in the scientific literature. Double disadvantage has also been reported in previous studies on oral epidemiology [21,22]. Oral health disparities related to racial/ethnic background among children were greater in wealthy schools than in deprived schools [21].…”
Section: Discussionsupporting
confidence: 75%
“…Double disadvantage has also been reported in previous studies on oral epidemiology [21,22]. Oral health disparities related to racial/ethnic background among children were greater in wealthy schools than in deprived schools [21]. Differences in dental care utilization between older adults with different levels of education were attenuated by country-specific dentist density [22].…”
Section: Discussionsupporting
confidence: 69%
“…Ethnic disparities in dental caries risk have been reported from all over the world [Matsuo et al, 2015;Delgado-Angulo et al, 2016]. Most studies were conducted in subjects having a permanent dentition, but we showed that these already exist during childhood.…”
Section: Discussionmentioning
confidence: 51%
“…They have a higher risk of being born preterm or postterm, having respiratory allergies, or having an adverse cardiovascular risk profile [Mehta et al, 2013;Gishti et al, 2015;Khanolkar et al, 2015]. Moreover, differences in oral health among ethnic groups have been reported by various studies from the Netherlands and other parts of the world [Truin et al, 2010;Wigen and Wang, 2010;Guarnizo-Herreño and Wehby, 2012;Schuller et al, 2014;Matsuo et al, 2015]. These studies indicate a higher prevalence of caries among children from immigrant or ethnic minority groups.…”
mentioning
confidence: 99%
“…Studies have indicated that people of certain races/ethnicities are more susceptible to dental caries due to their SES, local underlying cultural beliefs, ethnic origin, and other common risk factors (Matsuo et al 2015; Schluter and Lee 2016; van der Tas et al 2016). In China, several studies have also indicated the presence of oral health disparities among children of different ethnicities (Lo et al 2000; Leung and Chu 2003; Zhang et al 2014; Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 99%